A Meta-analysis of Effects of Computer Assisted Education on Students’ Academic Achievement: A-10-Year Review of Achievement Effect - Melih Dikmen, Murat Tuncer (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
The aim of this study is to determine the effect of computer-assisted education on the academic achievement of students through using meta-analysis method, defined as the interpretation of quantitative data. Meta-analysis studies are statistically analyzed for numerical data obtained from independent studies in similar subjects. Certain criteria are used to determine which researches will be included in the meta-analysis process. 43 experimental studies published between 2007 and 2017 were included in the study. As a result of the meta-analysis, the effect of computer-assisted education on student’s academic achievement was determined to be 1.028 level according to the random effect model. The effect of computer-assisted education on student’s academic achievement is found to be strong considering Cohen’s effect size range.